Comparison of Patient Perception of Nurse Caring Behavior in the Internal Room of the Hospital. Dr.H.Aloe Saboe, Gorontalo City and Dr. M.M. Dunda Limboto Hospital - Nur Rahmatia Akuba; Sabirin B. Syukur; Euis Herawati Hidayat (Universitas Muhammadiyah Palu, 2026)
Nurse caring behavior is an important component in improving the quality of nursing services because it is related to the quality of interaction between nurses and patients during the treatment process. Patients' perceptions of caring behavior can be used as an indicator in evaluating nursing services in hospitals. This study aims to determine the comparison of patients' perceptions of caring behavior of nurses in the inpatient room of Prof. Dr. H. Aloe Saboe Hospital and Dr. M.M. Dunda Limboto Hospital. The study used a comparative quantitative design with a cross sectional approach. The research sample amounted to 90 respondents consisting of 45 respondents each in both hospitals with purposive sampling techniques according to inclusion criteria. Data were collected using questionnaires that included indicators of presence, touch, listening, and understanding of patients, then analyzed univariately in the form of frequency and percentage distributions and bivariously using the Mann–Whitney test. The results of the study showed that in the attendance indicator, the percentage of good categories at Aloe Saboe Hospital was higher (73.3%) than at Dunda Limboto Hospital (66.7%), while the sufficient category at Dunda Limboto Hospital was larger (33.3%) than at Aloe Saboe Hospital (26.7%). In the touch indicator, the comparison shows the largest difference, where the category of both at Aloe Saboe Hospital is 80.0% and at Dunda Limboto Hospital is 60.0%, while the category of sufficient at Dunda Limboto Hospital (40.0%) is higher than at Aloe Saboe Hospital (20.0%). In the listening indicator, the good category at Aloe Saboe Hospital was 80.0% and at Dunda Limboto Hospital was 70.0%, while the sufficient category was 20.0% and 30.0%, respectively. In the understanding indicator, the good category at Aloe Saboe Hospital was 69.5% and at Dunda Limboto Hospital was 60.0%, while the sufficient category at Dunda Limboto Hospital (40.0%) was larger than Aloe Saboe Hospital (30.5%).